Multifunctional Carbon–Silica Nanocapsules with Gold Core for Synergistic Photothermal and Chemo‐Cancer Therapy under the Guidance of Bimodal Imaging. (6th April 2016) - Li, Linlin; Chen, Chuanfang; Liu, Huiyu; Fu, Changhui; Tan, Longfei; Wang, Shunhao; Fu, Shiyan; Liu, Xi; Meng, Xianwei; Liu, Hong
Abstract : Carbon‐based nanomaterials have been developed for photothermal cancer therapy, but it is still a great challenge to fabricate their multifunctional counterparts with facile methods, good biocompatibility and dispersity, and high efficiency for cancer theranostics. In this work, an alternative multifunctional nanoplatform is developed based on carbon–silica nanocapsules with gold nanoparticle in the cavity (Au@CSN) for cancer theranostics. The encapsulated chemodrug doxorubicin can be released from the Au@CSN with mesoporous and hollow structure in a near‐infrared light and pH stimuli‐responsive manner, facilitating spatiotemporal therapy to decrease off‐target toxicity. The nanocapsules with efficient photothermal conversion and excellent biocompatibility achieve a synergistic effect of photothermal and chemotherapy. Furthermore, the nanocapsules can act as a multimodal imaging agent of computed tomography and photoacoustic tomography imaging for guiding the therapy. This new design platform can provide a promising strategy for precise cancer theranostics. Abstract : Multifunctional carbon–silica nanocapsules with gold core are fabricated for cancer theranostics. The design integrates bimodal computed tomography, photoacoustic tomography imaging, and the synergistic effect of photothermal and chemotherapy under near‐infrared (NIR) light. NIR and pH‐responsive drug release efficiently increase the therapeutic effect and decrease off‐target toxicity.